Pharmacobezoar After Venlafaxine and Oxazepam Overdose: How Pharmacokinetics Could Help?—A Grand Round. Issue 2 (April 2021) - Laurent, Raphaël; Varvat, Cécile; Goudard, Delphine; Delavenne, Xavier; Gauthier, Vincent; Launay, Manon
Abstract : Abstract: The authors present here a case of a pharmacobezoar after drug overdose, diagnosed using multiple blood samples for TDM. This grand round highlights the importance of a dialog between a clinician and a TDM consultant for the optimal care of a patient.